Deciphering the hormonal signalling network behind the systemic resistance induced by Trichoderma harzianum in tomato - Martinez-Medina, Ainhoa; Fernandez, Ivan; Sánchez-Guzmán, Maria J.; Jung, Sabine C.; Pascual, Jose A.; Pozo, Maria J. (Frontiers in Plant Science, 2013)
Root colonization by selected Trichoderma isolates can activate in the plant a systemic defence response that is effective against a broad spectrum of plant pathogens. Diverse plant hormones play pivotal roles in the regulation of the defence signalling network that leads to the induction of systemic resistance triggered by beneficial organisms (ISR). Among them, jasmonic acid (JA) and ethylene (ET) signalling pathways are generally essential for ISR. However, Trichoderma ISR (TISR) is believed to involve a wider variety of signalling routes, interconnected in a complex network of cross-communicating hormone pathways. Using tomato as a model, an integrative analysis of the main mechanisms involved in the systemic resistance induced by Trichoderma harzianum against the necrotrophic leaf pathogen Botrytis cinerea was performed. Root colonization by T. harzianum rendered the leaves more resistant to B. cinerea independently of major effects on plant nutrition. The analysis of disease development in shoots of tomato mutant lines impaired in the synthesis of the key defence related hormones JA, ET, salicylic acid (SA) and abscisic acid (ABA) and the peptide prosystemin (PS) evidenced the requirement of intact JA, SA and ABA signalling pathways for a functional TISR. Expression analysis of several hormone related marker genes point to the role of priming for enhanced JA-dependent defence responses upon pathogen infection. Together, our results indicate that although TISR induced in tomato against the necrotrophs is mainly based on boosted JA-dependent responses, the pathways regulated by the plant hormones SA- and ABA are also required for successful TISR development